Efficiency Effects of Bank Mergers and Acquisitions - H.P. Huizinga; J.H.M. Nelissen; R. Vander Vennet (Tinbergen Institute, 2001)
Next to technological progress and deregulation, theintroduction of the euro is widely considered to be an importantcatalyst for bank consolidation in Europe. In order to assessthe public policy issues surrounding bank mergers, this paperanalyzes the efficiency effects of 52 horizontal bank mergersover the period 1994-1998, i.e. the period immediately precedingthe start of EMU. We find evidence of substantial unexploitedscale economies and large X-inefficiencies in European banking.The dynamic merger analysis indicates that the cost efficiencyof merging banks is positively affected by the merger, while therelative degree of profit efficiency improves only marginally.We do not find any evidence that merging banks are able toexercise greater market power in the deposit market. Hence, thebank M&As in this study appear to be socially beneficial.
Keywords: 330; Übernahme; Bank; Horizontale Integration; X-Effizienz; Skalenertrag; Wirtschaftliche Effizienz; EU-Staaten